KORELASI ANTARA MINAT MEMBACA DENGAN KEMAMPUAN BELAJAR PESERTA DIDIK - Fortin Boy Zega (Sekolah Tinggi Teologi Duta Panisal, 2020)
This research is motivated by the low interest in childrens reading that affects the ability to learn in the cognitive realm. Students need to have an interest in reading to achieve learning abilities in the cognitive realm. The formulation of the problem in this study are (1) Is there a correlation between reading interest with students learning abilities; (2) What is the percentage correlation between reading interest and students learning abilities. The method used by researchers is a quantitative method with research design Design One Shoot Case Study Experiment. The reason for use is because there are groups that are given treatment. Data collection techni2716-2885ques used by questionnaire researchers. While the data analysis technique used to test the hypothesis is a simple linear regression and correlation test with the help of IBM SPSS Statistics 23. The results show that, (1) There is a correlation between reading interest and students learning abilities; (2) There is a very significant correlation between reading interest and students' learning abilities with a percentage of 3.3% or 0.533.